Periodontal Management of Cyclosporin A-Induced Gingival Overgrowth: A Nonsurgical Approach - Rayhana Malek; Bouchra El Houari; Jamila Kissa (Case Reports in Dentistry)
Gingival overgrowth is a major and frequent unwanted effect accompanying the chronic usage of antihypertensive, anticonvulsant, and immunosuppressant drugs. The expression and the severity of this tissue-specific condition are influenced by a variety of factors, mainly drug and periodontal variables. Such increased volume of gingiva may compromise normal oral functions, aesthetics in addition to the patients’ ability to practice optimal oral hygiene. The management of gingival overgrowth includes nonsurgical approach, surgical approach, or both of them for severe cases of gingival overgrowth as well as drug withdrawal. This case report illustrates a successful nonsurgical management of a 21-year-old patient with cyclosporin A-induced gingival overgrowth who experienced a total regression of the gingival enlargement without any surgical procedure or drug substitution. And it highlights therefore the key role of supportive periodontal therapy in maintaining good and stable outcomes over 2 years of follow-up.